Study on the Assessment Model of Video Communication Quality Based on Smart Terminal - Jianting Han; Su Zhang (Dianxin kexue)
Nowadays operators are focusing on developing the video communication services based on smart terminals.The characteristics and key affecting factors of video communication quality were discussed.Furthermore，according to the analysis of the methods of subjective and objective video quality assessment，an assessment model of video communication service quality was proposed and verified by experimental data，which can provide test reference and evaluation methods for operators to improve the quality of video communication service.